New trends in mechanical engineering and materials : selected, peer reviewed papers from the 2012 International Conference on Mechatronics and Materials Engineering (ICMME 2012), July 13-14, 2012, Hangzhou, China - Deng, Xiancang; Dong, Xufeng (Applied mechanics and materials, 2013)
The collection includes selected, peer reviewed papers from the 2012 International Conference on Mechatronics and Materials Engineering (ICMME 2012) held July 13-14, 2012, in Hangzhou, China. The 94 papers are grouped into the following chapters: Chapter 1: Mechanical Engineering; Chapter 2: Mechatronics; Chapter 3: Computer Aided Design in Mechanical Engineering; Chapter 4: Applied Materials: Study, Structure, and Technologies. Review from Book News Inc.: The conference was initially created by researchers and engineers in mechatronics and materials engineering. The 90 papers cover mechanical.